Youth Psychotherapy Change Trajectories and Early Warning System Accuracy in a Managed Care Setting. Issue 9 (4th February 2013) - Nelson, Philip L.; Warren, Jared S.; Gleave, Robert L.; Burlingame, Gary M.
<x xml:space="preserve">Abstract</x> Objectives To examine change trajectories in routine outpatient mental health services for children and adolescents in a managed care setting, and to use these trajectories to test the accuracy of two variations of an early warning system designed to identify cases at risk for deterioration. Method Multilevel modeling procedures were used to examine longitudinal Youth Outcome Questionnaire (YOQ) data for 16, 091 youth aged 4‐17 years (39% female, mean age 10.5) referred for treatment in a managed care system. Results Clients with more frequent YOQ administrations had slightly lower baselines and faster rates of change. Both the traditional and simplified versions of the early warning system demonstrated good accuracy in identifying clients who deteriorated, with a sensitivity of .63, specificity of .83, and hit rate of .81. Conclusions Results provide further evidence that patient‐focused early warning systems can accurately identify most youth who are at risk for negative outcomes in routine mental health services.